Efficacy of Combination Dutasteride and Lycopene to Reduce Bleeding in Benign Prostate Hyperplasia (BPH) Post- Transurethral Resection of the Prostate (TURP) Overview of Hypoxia inducible factor-1 alpha (HIF-1 α) Expression and Hematocrit Levels - Eriawan Agung Nugroho; Siti Amarwati; Nugroho Akhbar (Majalah Obat Tradisional, 2020)
Trans Urethral Resection of the Prostate (TURP) is one of the gold operating standards for people with Benign Prostate Hyperplasia (BPH), but the complications, like bleedings, often occur both in durante and post-surgery. The risk of bleeding in TURP is caused by angiogenesis. Hypoxia-Induced Factor-1 Alpha (HIF-1 α) is one of the trigger factors for angiogenesis in BPH. Based on the existing literature, it was found that there was a relationship between lycopene and dutasteride which both had a synergistic effect in inhibiting angiogenesis. However, the mechanism is unknown. This study aims to assess the effectiveness of the combination of dutasteride and lycopene on the expression of HIF-1α and hematocrit levels in BPH patients undergoing TURP surgery. This research was an experimental study with "Double-Blind Randomized Controlled Trial Post Test Only Design". The 22 patients were divided into 2 groups, namely T (dutasteride + lycopene), C (lycopene+plasebo), which were given every 24 hours for a minimum of 30 days until the TURP operation was carried out. The observation of HIF-1α expression used immunohistochemical methods. Different tests were conducted between the groups with Independent T-test. The result shows the combination of dutasteride and lycopene was not significant in reducing the HIF-1α expression, indicated by mean rank in the group (C) (= 21.60), group (T) (= 20.00). The results obtained from the Independent   T-test were (p = 0.410), meaning the difference in HIF-1α expression between the 2 groups was not significant: Average Δ Ht group C (= 1.26); group T (= -0,98). The statistical test with the Independent T-test obtained (p = 0.027), where there were significant differences. Giving a combination of dutasteride and lycopene for at least 30 days pre-TURP surgery was not effective in reducing the expression of hypoxia-induced factor - 1 alpha (HIF-1α) but was effective in reducing hematocrit levels compared to a single administration of dutasteride in BPH patients undergoing TURP surgery.